Avaliação de aspectos fluidodinâmicos e da transferência de calor em leito fixo com escoamento gás-líquido concorrente vertical - Moreira, Marcos Flávio Pinto (Universidade Federal de São Carlos, 2004)
In this work, the heat transfer in packed bed with gas-liquid co-current downflow and upflow was investigated. The influence of hydrodynamic factors, of the size and shape of particles, of the length of the thermal section and of the direction of flow on thermal parameters were evaluated. At first, a study about the hydrodynamic behavior (flow regimes and liquid saturation) were carried out. It was verified that flow regimes and liquid saturation were affected by gas and liquid flow rates and particle characteristics (shape and size). Five pseudo-homogeneous models were evaluated in order to obtain the thermal parameters. The traditional model to two-parameters was chosen because it presented good fits and more reliable parameters. The heat transfer was higher in upflow than in downflow. The temperature profiles obtained were flat in some conditions in upflow. The wall-heat transfer coefficient (hW) was affected by the length of the thermal section and mainly, by liquid flow rate in both downflow and upflow. The radial effective thermal conductivity (kr) also was affected by the length of the thermal section and liquid flow rate. The gas flow rate affected this parameter in upflow. Besides, the particle characteristics, shape and mainly size, affected kr.
Keywords: Calor - transmissão; Leito fixo; Condutividade térmica; Escoamento ascendente e descendente; Gás-líquido; CIENCIAS EXATAS E DA TERRA::FISICA::AREAS CLASSICAS DE FENOMENOLOGIA E SUAS APLICACOES::TRANSFERENCIA DE CALOR; PROCESSOS TERMICOS E TERMODINAMICOS